The second Arab awakening and the battle for pluralism - Muasher, Marwan (Yale University Press, 2014)
This important book is not about immediate events or policies or responses to the Arab Spring. Instead, it takes a long, judicious view of political change in the Arab world, beginning with the first Awakening in the nineteenth century and extending into future decades when--if the dream is realized--a new Arab world defined by pluralism and tolerance will emerge.